FGFR inhibitors promote the autophagic degradation of IFN-γ-induced PD-L1 and alleviate the PD-L1-mediated transcriptional suppression of FGFR3-TACC3 in non-muscle-invasive bladder cancer - Yu-Chen Lin; Cheng-Ying Chu; Tsung-Han Hsieh; Bo-Jyun Lin; Jing-Ping Liou; Yun Yen; Chun-Han Chen (Cell Death and Disease)
Abstract Bladder cancer (BC) is the second most prevalent genitourinary malignancy worldwide. Treatment options remain limited for patients with Bacillus Calmette–Guérin (BCG)-unresponsive non-muscle-invasive bladder cancer (NMIBC). Up to 70% of NMIBC cases harbor fibroblast growth factor receptor 3 (FGFR3) alterations, and FGFR inhibition has shown potential to enhance the efficacy of immune checkpoint inhibitor (ICI). Interferon (IFN)-γ, a cytokine produced by activated T cells and associated with better response to immunotherapy in BC, is a key inducer of PD-L1 expression in the tumor microenvironment. However, the interaction between FGFR inhibitors and IFN-γ-induced PD-L1 expression in FGFR3-activated NMIBC cells remains unclear. Here, we show that FGFR inhibitors significantly reduced IFN-γ-induced PD-L1 expression in NMIBC cells harboring FGFR3-TACC3 fusions. Mechanistically, FGFR inhibitors restored IFN-γ-suppressed SIRT1 expression, promoted LC3B deacetylation and nuclear export, and enhanced autophagy-lysosomal degradation of PD-L1. Blocking autophagy, overexpression SIGMAR1, or inhibiting lysosomal activity significantly reversed PD-L1 degradation. Notably, we demonstrate for the first time that IFN-γ-induced PD-L1 directly binds to the FGFR3 promoter and represses FGFR3-TACC3 transcription–an effect that can be rescued by FGFR inhibitors or PD-L1 knockdown. Functionally, FGFR inhibitors ameliorated PD1/PD-L1-mediated T cell suppression in co-culture assays. Together, these findings highlight a novel mechanism by which FGFR inhibitors suppress IFN-γ-induced PD-L1 via autophagy and suggest a potential strategy to improve ICI therapy in FGFR3-altered NMIBC.